The Limits of Homage: Image and Memories in Teatro Abierto 2013 (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In 2013, within the context of the 30th anniversary of the democratic recovery after the last civic-military dictatorship in Argentina, the Public Television organized a cycle of programs to pay homage to Teatro Abierto 1981 (TA). The article analyzes this TV program as part of the social memory of cultural resistances, in a period (2003-2015) when the building of memories of state terrorism became center stage in the public sphere, and in the government’s agenda. The article focuses on the live conversations on TV, between the host and individuals who participated either in the 1981 experience or in its homage, 32 years afterwards. It inquires into what was said and what was silenced; it looks into the dialogues that took place on screen and the interruptions of those dialogues. It argues that the testimonies ended up losing memorial depth because they reiterated the epic, well-known, and already legitimate narrative of TA. The article suggests that the TV program was not permeable enough to an open-ended and exemplary memory, able to value TA within a genealogy of movements, within and outside the theater field, and beyond state terrorism.
Keywords: Teatro Abierto; Social Memory; Television; Sociocultural Movement.